Cooperation in distributed surveillance systems for dense regions. (1st January 2011) - Benaskeur, Abderrezak; Khamis, Alaa; Irandoust, Hengameh
In this paper, we envision a distributed surveillance system where spatially distributed sensors of different modalities can sense collaboratively and continuously large-scale, dynamic, dense and semi-structured environments. The paper discusses surveillance operations in complex and dense environments, such as littoral regions, and describes the key features of distributed surveillance systems. Effective and robust cooperation among the artificial and/or the human agents can synergistically improve the performance of these systems and can endow them with higher-level faculties, such as cooperative target detection and tracking. Different forms of cooperative activities in distributed surveillance systems are mentioned. The paper focuses on intra and inter-platform target cueing and handoff as augmentative forms of cooperation in distributed surveillance.